Erythrocytic cation transport receptor numbers and activity in pregnancies complicated by essential hypertension and pre-eclampsia. Issue 6427 (5th May 1984) - Aronson, J K; Moore, M P; Redman, C W; Harper, C
Abstract : Various functions of erythrocytic cation transport were studied in normotensive and hypertensive pregnancy (women with pre-eclampsia and essential hypertension). The results showed that in pregnancy there is an increase in the number of erythrocytic glycoside binding sites accompanied by a proportional increase in the active inward transport of rubidium (used as a substitute for potassium). There was no evidence of an effect of pregnancy on intraerythrocytic sodium concentrations. These changes were apparently entirely attributable to pregnancy and not affected by pre-eclampsia or essential hypertension. It is suggested that these alterations indicate an adaptive increase in sodium pump numbers and activity secondary to a tendency for the intraerythrocytic sodium concentration to rise during pregnancy and compensating for that tendency.